PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN - Sulistyowati, Sulistyowati; Fidiana, Fidiana (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
The purpose of this research is to analyze the influence of good corporate governance to the financialperformance which consists of board of director, board of commissioner, independent commissioner, and auditcommittee to the financial performance of banking companies in Indonesia in 2012-2014 periods.The sampleshave been selected by using purposive sampling technique, based on the determined criteria 30 companies havebeen selected as samples. The result of this research shows that: (1) Board of directors has positive influencebecause the greater number of the board members can lead to more conflicts, but the number can provide analternative solution to a problem that is increasingly diverse in board members (2) Board of commissioners haspositive influence because when the member of commissioners that much , the control to the board of directors isgetting better (3) Independent commissioner doesnât have influence because the existence of independentcommissioner in a company is formality only to fulfill the regulation(4) Audit committee doesnât have influencebecause the duties of audit committee is to help the board of commissioners to control the reporting process offinancial statement by the management to improve the credibility of financial statements.Keywords: Good Corporate Governance, Board of Directors, Independent Commissioners, Audit Committee,CFROA.